KEPUASAN PASIEN PADA PEMBERIAN PIO PENJUALAN SWAMEDIKASI TERHADAP CUSTOMER LOYALTY DI APOTEK SYARINA KABUPATEN SEMARANG - Fitriani, Sefia; Suwarni, Sri; Wulandar, Ratna; Rustaman, Heri; Kusumaningtyas, Aprilia (Jurnal Farmasi & Sains Indonesia, 2023)
Pharmaceutical services are currently developing along with increasing public awareness of the importance of health. A pharmacy is a means for carrying out pharmaceutical work and a means for serving pharmaceutical supplies to the community. One of the pharmaceutical jobs carried out in pharmacies is Drug Information Services. The purpose of this study was to analyze the relationship between patient satisfaction in giving drugs informations for self-medication sales to customer loyalty at the Syarina Pharmacy, Semarang Regency. This research is a quantitative research using survey method. Data was collected by purposive sampling method and using the Slovin formula to determine the sample size and population. The research subjects were all customers who received drug information services on self-medication at the Syarina Pharmacy, Semarang Regency using the Pearson correlation analysis method. The results of the analysis show that there is a relationship between the level of patient satisfaction and customer loyalty at the Syarina Pharmacy with siq = 0.00